ANALYSIS OF THE NEEDS AND CHARACTERISTICS OF PAI STUDENTS IN THE DIGITAL AGE BASED ON THE MERDEKA CURRICULUM - Fitriyanti Fitriyanti; Lenny Misdiyanti; Abdurrahmansyah Abdurrahmansyah; Nurlaila Nurlaila (Jurnal Konseling Pendidikan Islam, 2026)
Islamic Religious Education (PAI) in the digital era faces serious challenges due to fundamental shifts in the characteristics and learning needs of students who are increasingly immersed in digital ecosystems. This study aims to analyze the characteristics and learning needs of PAI students in the digital era as a basis for developing Merdeka Curriculum-based learning designs. A qualitative approach was employed using library research method through content analysis of relevant scientific literature. The findings reveal that PAI students in the digital era are characterized as digital natives with visual and interactive learning preferences; they require contextual content, varied digital media, active-collaborative methods, and differentiated approaches. The learning environment is marked by opportunities such as expanded access and gamification, while simultaneously threatened by digital distraction and unverified religious content. Based on these findings, a responsive PAI learning design under the Merdeka Curriculum can be constructed upon five core principles: differentiated learning, pedagogical technology integration, Pancasila Student Profile reinforcement, Islamic project-based learning, and authentic digital assessment.